2022
DOI: 10.1186/s13020-022-00600-z
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of combined chinese herbal medicine and western medicine therapy for COVID-19: a systematic review and meta-analysis

Abstract: Objective To systematically review the clinical efficacy and safety of Chinese herbal medicine (CHM) with and without Western medicine (WM) for different severity of COVID-19. Methods CNKI, PubMed, Wanfang Database, ClinicalTrails.gov, Embase, ChiCTR and ICTRP were searched from 01 Jan, 2020 to 30 Jun, 2021. Two authors independently assessed all the randomized clinical trials (RCTs) for trial inclusion, data extraction and quality assessment. Meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Relevant systematic reviews concerning CHM efficacy assessment have been published, but with limitations ( 22 29 ). Some articles incorporated non-RCTs (e.g., observational studies), or pooled the data from non-RCTs and RCTs together ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant systematic reviews concerning CHM efficacy assessment have been published, but with limitations ( 22 29 ). Some articles incorporated non-RCTs (e.g., observational studies), or pooled the data from non-RCTs and RCTs together ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many articles didn't assess the certainty of evidence ( 23 25 , 27 , 28 ). Some failed to address the risk of bias for each outcome due to the inappropriate use of Cochrane Risk of Bias Tool 2.0 (RoB2) ( 22 , 26 , 29 ). A previous systematic review has only pooled the outcomes with low risk of bias, which could lead to omission of evidence ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the overall quality of RCTs studies included in this review was generally poor, a finding commonly reported in previous systematic reviews involving TCM for other conditions [ 147 150 ]. Among 82 included trials, none of them were completely in compliance with CONSORT-CHM guideline.…”
Section: Discussionmentioning
confidence: 96%
“…Other WMs, such as lopinavir/ritonavir and favipiravir, also have similar concerns [13,29]. In contrast to WM, TCM has unique features, including multi-target, multi-pathway approach and multi-component, which are beneficial for anti-inflammatory, organ protection, broadspectrum antiviral, and immune regulation [30,31]. Thus, compared with WM, TCM is associated with fewer side effects.…”
Section: Discussion About Tcm and Wmmentioning
confidence: 99%